Transaction Intensity on Electronic Marketplace in Indonesia: Study of Clothing Product Purchases Based on Transactional Data - I Nyoman Agus Wirya WP*; Vid Adrison (Riwayat: Educational Journal of History and Humanities, 2023)
This research studies the impact of time trends on transaction intensity through electronic marketplaces, especially in purchasing high-risk products such as clothing. We monitored the intensity of clothing product transactions since the first purchase of 60,341 sample accounts from January 2018 to December 2019. We estimate log-linear model parameters with random effects from unbalanced panel data involving several control variables. The results show that the transaction intensity has decreased over time since the first purchase. This indicates consumers accept risks that exceed benefits, or in other words, the courage to transact through the electronic marketplace is decreasing for the purchase of clothing products.